Overview Of Nurse's Workload In The Emergency Room Of The Undata Hospital, Central Sulawesi Province - Setiyawan, Agus Eri (Tadulako University, 2020)
In Undata hospitals there are 31 nurses in the emergency room. This is not comparable to the number of emergency room visits in the last three years, which increased from 2016 as much 13,571 people, 2017 increased by 14,508 people, and 2018 sending 15,597 people. Whereas the average number of patient visits each day is 60 patients. Based on the calculation formula according to Gillies (1994) in Idris (2017), the emergency room requires 36 nurses. While nurses in the emergency room Undata Hospital only amounted to 31 people. This study aims to look at the description of the workload of nurses in the Emergency Room Installation (IGD) Undata Hospital of Central Sulawesi Province. This type of research uses quantitative research with a descriptive approach. The research sample of 31 respondents with inclusion criteria nurses who work in the emergency room and nurses who are not in a state of work and education leave. The results showed that direct nursing activities, namely respondents stated weight as much as 31 people (100%), and indirect nursing activities, namely respondents stated weight as much as 31 people (100%). Hospital management should pay attention to the nurses workload again, by increasing the number of nurses in the emergency room, referring to the Republic of Indonesia Ministerial Regulation No. 340 article 11 of 2010, type B hospital care ratio that is 1 nurse serving 1 patient and evaluating performance nursing regularly to improve the quality of nursing care.